A proposed supplementary social studies content for MSU-SCTO community high schools with emphasis on Islamic culture - Madjailand, Musha Dayani
The author aimed to look into how the proposed supplementary social studies content with emphasis on Islamic culture is presented in the second and fourth year high school students.